Impact of the coxsackievirus and adenovirus receptor on the adenoma-carcinoma sequence of colon cancer - Stecker, K.; Vieth, M.; Koschel, A.; Wiedenmann, B.; Röcken, C.; Anders, M. (British Journal of Cancer, 2011)
Background:Coxsackie and adenovirus receptor (CAR) has been suggested to function as a tumour suppressor. Its impact on the adenoma-carcinoma sequence of the colon, however, is unclear.Methods:Coxsackie and adenovirus receptor was analysed in non-cancerous and neoplastic colon samples using immunohistochemistry and quantitative RT-PCR. The function of CAR in colon cancer cell lines was determined following application of CAR siRNA or ectopic expression of a human full-length CAR cDNA.Results:Compared with healthy mucosa, increased CAR-mRNA expression was found in adenomas, whereas primary cancers and metastases displayed a marked decline. At the plasma membrane, CAR was present in normal mucosa samples (93%), adenomas, and metastases (100% ea.), whereas in colon cancers, it was found less frequently (49%, P0.0001). Cytoplasmic CAR immunopositivity increased from normal mucosa (22%), to adenomas (73%, P0.0006), primary cancers (83%, P0.0001), and metastases (67%, P0.0019). In cancer cell lines, CAR inhibition resulted in increased proliferation, whereas enforced ectopic CAR expression led to opposite results. Blocking the extracellular portion of CAR increased cell invasion in vitro. In mice, xenotransplants of colon cancer cells with enforced CAR expression formed significantly smaller tumours, whereas CAR inhibition increased the formation of liver metastases.Conclusion:We conclude that CAR facilitates complex effects during colon carcinogenesis, potentially mediated by its stage-dependent subcellular distribution; high CAR expression potentially prevents apoptosis in adenomas, loss of CAR at the plasma membrane promotes growth, and dissemination of primary cancers, and high membranous CAR presence may support the establishment of distant metastases. © 2011 Cancer Research UK All rights reserved.
CRIS-Team Scopus Importer:2025-03-05
Keywords: adenoma-carcinoma sequence; colon cancer; coxsackie adenovirus receptor